2006
DOI: 10.1097/01258363-200609000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of oral health recommendations into two residential aged care facilities in a regional Australian city

Abstract: Background Residents of aged care facilities usually have a large number of oral health problems. Residents who suffer from dementia are at particular risk. A systematic review of the best available evidence with regard to maintaining the oral health of older people with dementia in residential aged care facilities provided a number of recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…This information could then be used to determine the patient's oral care needs. Fallon et al . reported that oral care plans were not routinely filled out by residential aged care nurses.…”
Section: Discussionmentioning
confidence: 99%
“…This information could then be used to determine the patient's oral care needs. Fallon et al . reported that oral care plans were not routinely filled out by residential aged care nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Planning and implementing practice procedures such as an entry level oral health assessment and 'accountability for oral health being done' (OHT1) requires organisational commitment that is considered integral to the process of improvement 7,17,18 . These challenges were identified across contexts including education, clinical practice and organisational management.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect a broader policy trend as a legal change in the Netherlands in 2006 allowed clients to approach a dental hygienist directly 15,16 . The appointment of such roles is reported to be a cost-effective option for improving oral health knowledge, skills and motivation for staff 7,17,18 . More recent literature adds that the oral health champion has to be accessible and have rapport with the group targeted for change 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate care. In many countries, such as Canada 14,47 and the USA 48 , caregivers are legally, ethically and morally responsible to provide the same care for disabled as for abled people 49,50 , and government-regulated LTC facilities in Australia are required to provide oral care and access to dentists 51,52 . Yet there are serious gaps in integration of oral health care with general health care 16,36,[53][54][55] .…”
Section: Frequency Of Practicementioning
confidence: 99%